Global overview of suicidal behavior and risk factors among the general population during the COVID-19 pandemic: a scoping review - Sriyani Padmalatha Konara Mudiyanselage; Yi-Tseng Tsai; Yi-Jing Tsai; Ya-Han Yang; Zan-Ting Lu; Nai-Ying Ko (BMC Psychology)
Abstract Background The COVID-19 pandemic, declared by the World Health Organization in early 2020, rapidly escalated from a global health crisis to a significant public health issue worldwide. This scoping review aims to provide a comprehensive global overview of suicidal behavior and associated risk factors during the COVID-19 pandemic. Methods Adhering to the PRISMA 2020 guidelines, literature searches were conducted across five databases: Embase, MEDLINE, CINAHL, Web of Science, and Academic Search Complete. The review encompassed studies published from January 1, 2019, to November 29, 2023. A total of 286 studies met the inclusion criteria, offering a broad perspective on suicidal behaviors during the pandemic. The studies underwent quality assessment using the Joanna Briggs Institute (JBI) Critical Appraisal for Checklist for Prevalence Studies Scale (CACPSS). Results The highest rates of suicidal behavior were observed in the Americas, Europe, and the Western Pacific Region, with China and the United States reporting significant cases. Key risk factors included demographic characteristics, mental health conditions, and social support factors. Suicidal ideation prevalence rates ranged significantly, with the highest in some regions exceeding 50%. Suicide attempts and completed suicides also showed considerable variation across different countries and regions. Conclusion The findings emphasize the need for targeted mental health interventions and policies to reduce suicide risk, highlighting the multifaceted nature of suicidal behaviors during the COVID-19 pandemic. Comprehensive, multidisciplinary approaches are necessary to address this pressing concern, and understanding the interplay among diverse risk factors is crucial for developing effective prevention and intervention strategies.